If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 = 6u + -2 Reorder the terms: 4 = -2 + 6u Solving 4 = -2 + 6u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-6u' to each side of the equation. 4 + -6u = -2 + 6u + -6u Combine like terms: 6u + -6u = 0 4 + -6u = -2 + 0 4 + -6u = -2 Add '-4' to each side of the equation. 4 + -4 + -6u = -2 + -4 Combine like terms: 4 + -4 = 0 0 + -6u = -2 + -4 -6u = -2 + -4 Combine like terms: -2 + -4 = -6 -6u = -6 Divide each side by '-6'. u = 1 Simplifying u = 1
| 4+11k=103 | | 30*32*9= | | 6-3u=18 | | 12*3.14= | | -16=3z+5 | | 5*3.14= | | 11*3.14= | | -20=7-3q | | 9*3.14= | | 10x+4x=126 | | 9n-3(2n-1)=12 | | SV+2=52 | | 2k+1=19 | | 7*3.14= | | 4z+4=32 | | 6*3.14= | | 4x-2(3y-5)= | | 450*5.25*2.5= | | 5-3*K=19 | | 3x=44-9x | | 6x^2+24=0 | | 15x=27+12x | | 9+11x=29+9x | | 17x-3=16x+9 | | 8x+6=5x+36 | | 5x+3.5=8 | | 5x^2+4xy*5y^2=0 | | 6x+17=41 | | a+(a+1)+(a+2)=72 | | 8x+14=38 | | 7x-(-10)=-39 | | y+12= |